2015
DOI: 10.1007/s00403-015-1574-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial structural integrity is important for adipose regeneration after transplantation

Abstract: Advances in structural fat transplantation technology have significantly improved the survival rate and stability of grafts. This study investigated the importance of the spatial structural integrity of adipose tissue for adipose regeneration after fat transplantation. We sought to enhance understanding of structural fat transplantation and optimize procedures used for the clinical acquisition, purification, and transplantation of adipose tissue. In an inactivated structuration adipose tissue model established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Autologous fat grafting has become increasingly used as a method for multiple volume filling applications. The major obstacle to the widespread of its clinical use is the lack of standardized guidelines during harvesting, processing and implantation steps [ 91 ]. Indeed, many authors have recognized that there is no universally accepted methodology for fat grafting [ 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autologous fat grafting has become increasingly used as a method for multiple volume filling applications. The major obstacle to the widespread of its clinical use is the lack of standardized guidelines during harvesting, processing and implantation steps [ 91 ]. Indeed, many authors have recognized that there is no universally accepted methodology for fat grafting [ 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…64 In fact, it has recently been shown that decellularized fat may serve as a scaffold and be repopulated and revascularized after implantation, demonstrating the importance of the mechanical aspects of the adipose-specific niche. 65 The biomechanics of fat transfer therefore should not be ignored, and represent an appropriate lens through which to view the effects of fat procurement, processing, and placement.…”
Section: Placementmentioning
confidence: 99%
“…The activity of adipocytes is affected by fat preparation and processing methods (Oranges et al, 2019;Sese et al, 2019;Wei et al, 2019). The key factor contributing to the fat retention rate is the extent of retainment of the integrity and activity of the adipocyte structure in the fat graft (Yuan et al, 2015). In recent years, Kato et al (2014) proposed the three-zone theory of fat transplantation, based on two older theories: the cell survival theory, which states that only one to three layers of mature adipocytes could survive in grafts due to the lack of early blood supply and oxygen content, and the host cell replacement theory, indicating that new adipocytes are formed almost exclusively by the differentiation of ASCs (Billings and May, 1989).…”
Section: Discussionmentioning
confidence: 99%